A Growing Degree Day Model is Effective to Schedule Spring Defendor (Florasulam) Applications for Suppressing Dandelion Flowers. Issue 1 (22nd March 2018) - Patton, Aaron J.; Weisenberger, Daniel V.; Breuninger, James M.
Abstract : Core Ideas: Early spring Defendor (florasulam) applications effectively inhibit dandelion blooming. Apply Defendor prior to 75 accumulated growing degree days (base = 50°F) to suppress dandelion blooms. Defendor application timing is weeks earlier than traditional phenoxy herbicides.